Polybenzimidazoles based on 3,3 `-diaminobenzidine and aliphatic dicarboxylic acids: synthesis and evaluation of physicochemical properties toward their applicability as proton exchange and gas separation membrane material - Bhavsar, Rupesh S.; Nahire, Sandip B.; Kale, Mrunali S.; Patil, Shubhangi G.; Aher, Pradnya P.; Bhavsar, Ritesh A.; Kharul, Ulhas K. (Journal of Applied Polymer Science, 2011)
A series of aromatic-aliphatic polybenzimidazoles (PBIs) based on 3,3'-diaminobenzidine (DAB) and aliphatic dicarboxylic acid with incremental -CH2- groups were synthesized. Optimization of synthesis parameters and evaluation of physicochemical properties are requisite for PBI applicability as the proton exchange membrane (PEM) and gas separation membrane materials are reported. It was found that though all these PBIs exhibited high thermal, mechanical, and oxidative stability, effect of added flexibility on physical properties is not monotonous. Membranes were prepared by solution casting as well as phase-inversion method. The later types of membranes exhibited much higher H3PO4 content than its doping achieved in the solution casted membranes. These PBIs possess low hydrogen and helium permeability than that of conventional PBI. This low permeability, along with their excellent oxidative stability indicated that they can be promising PEM materials. Their CO2-sorption analysis revealed that PBI6 based on suberic acid possesses appreciable CO2 sorption. (C) 2010 Wiley Periodicals, Inc. J Appl Polym Sci 120: 1090-1099, 2011
Keywords: Gas permeation; mechanical properties; membranes; oxidative stability; polybenzimidazoles

Studies on nano composites of SPEEK/ethylene glycol/cellulose nanocrystals as promising proton exchange membranes - Bano, Saleheen; Negi, Yuvraj S.; Illathvalappil, Rajith; Kurungot, Sreekumar; Ramya, K. (Electrochimica Acta, 2019)
The present work deals with fabrication and characterisations of nano-composite membranes composed of sulfonated poly (ether ether ketone) (SPEEK) cross-linked and reinforced with ethylene glycol (EG) and cellulose nanocrystals (CNCs) respectively. The thin films of cross-linked composite membranes were prepared by solvent casting method and further analysed for physicochemical and electrochemical properties to execute their applicability as promising proton exchange membrane (PEM) in fuel cells. The process of cross-linking helps to improve the strength and dimensional stability of bare SPEEK membranes without compromising with conductivity. However, presence of CNCs further improves the strength and provides an effective pathway for the conduction of protons in membranes by interacting through their surface hydroxyl and sulfonic acid groups with ionic moieties of polymer matrix. All prepared composite membranes showed good oxidative and thermal stability along with good proton conductivity. The cross-linked SPEEK membranes with 4 wt% loading of CNCs possess an appreciable proton conductivity of 0.186 S/cm at 95 degrees C and 95% RH which is comparable to Nafion 117. From the view point of above studies, the prepared nano-composite can be described as promising proton exchange membrane for fuel cells. (c) 2018 Elsevier Ltd. All rights reserved.
Keywords: Cellulose nanocrystals; Cross-linked SPEEK; fuel cell; oxidative stability; proton conductivity